Self-directed career attitude as predictor of career and life satisfaction in Chinese employees: Calling as mediator and job insecurity as moderator. Issue 7 (9th November 2015) - Zhang, Chunyu; Hirschi, Andreas; Herrmann, Anne; Wei, Jia; Zhang, Jinfu
Abstract : Purpose: – The purpose of this paper is to test if the effects of a self-directed career attitude on career and life satisfaction are mediated by a person's sense of calling and moderated by job insecurity in a sample of Chinese employees. Design/methodology/approach: – Among a sample of Chinese employees ( n =263), in this paper, a moderated mediation analysis with bootstrapping was applied to test the hypotheses. Findings: – The results showed that calling mediates the effects of a self-directed career attitude on career satisfaction and life satisfaction. Job insecurity moderated the effect on life satisfaction but not on career satisfaction. The effect on life satisfaction were stronger under higher levels of job insecurity. Research limitations/implications: – These results suggest that a self-directed career attitude may help people develop a calling, which in turn relates to increased subjective career success and well-being. In addition, the notion of a calling may be especially important for well-being in unstable job circumstances. Originality/value: – This study is the first to explore a calling and a self-directed career attitude in a sample of Chinese employees. Corresponding to contemporary China's rapidly changing context of economy and career development, a self-directed career orientation plays an important role in Chinese employees' calling and subjective career success.